Perceived need of health care and barriers in access to health services among migrants in Portugal. (20th October 2021) - Gama, A; Marques, MJ; Pedro, AR; Mendonça, J; Fernandes, AC; Dias, S
Abstract: : Health care has been pointed out as a key determinant of migrants' health and social integration, but there is evidence of disparities in its access across subgroups. A deeper understanding of the barriers in access to health care, particularly among vulnerable groups, is needed. Our study aims to examine perceived need of health care, access to health services and barriers among migrants in Portugal. A cross-sectional survey was conducted with 1126 adult migrants (53.4% females), originated from African, Middle East, Asian countries and Brazil, living in Portugal for no longer than 10 years. The collected data included sociodemographic characteristics, perceived need of health care, access to health services and difficulties experienced. Differences between groups were analysed through chi-square tests. Results showed that most of the participants (64.7%) have needed health care in the previous 12 months in Portugal. Of these, 87.8% accessed a health care service. However, even needing health care, 3.3% decided not to seek care and 8.8% were not able to access a health care service. Reporting no access to health care was more frequent among migrants with shorter length of stay in the country (<1 year: 19.4% vs. 1 to 5 years: 7.3% and 6 to 10 years: 4.6%; p = 0.001) and those with non-regular migration status (in regularisation process: 11.5% and undocumented: 9.5% vs. documented: 7.2%; p = 0.040). Most common barriers were lack of the National Health Service user card (38%), financial constraints (15%), undocumented status (11%) and language difficulties (7%). Although efforts have been made over the past decades in Portugal to adopt inclusive policies and promote migrants' access to health care, strategies are needed to improve information on migrants' health rights, especially of those undocumented and recently arrived. Economic and language difficulties should be further addressed in comprehensive interventions to promote equal access to health care. Key messages: Migrants residing in the country for less than a year and those with non-regular migration status reported more frequently not being able to access health care. Despite the efforts to adopt inclusive policies and promote migrants' access to health care, strategies are needed to improve information on migrants' health rights and promote equal access to care.